∫ sin ( 1 0 1 x ) sin 9 9 x d x
If the indefinite integral above equals k sin ( a x ) ( sin x ) b + C where a , b and k are constants and C is the arbitrary constant of integration, find a + b + k .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
See here
Log in to reply
Great ! But another solution can be wriring these sines using Euler's formulas (using exponentials...) and things will get clearer!
Another way to solve this question is to directly differentiate the expression k sin ( a x ) ( sin x ) b + C with respect to x , by differentiation - chain rule ,
d x d k 1 [ sin ( a x ) ( sin x ) b ] = = k 1 [ b sin ( a x ) ( sin x ) b − 1 cos x + a cos ( a x ) ( sin x ) b ] k 1 ( sin x ) b − 1 [ b sin ( a x ) cos x + a cos ( a x ) sin x ]
Since the aforementioned expression is equal to sin ( 1 0 1 x ) sin 9 9 x , this suggest that ( sin x ) b − 1 = ( sin x ) 9 9 ⇒ b − 1 = 9 9 ⇔ b = 1 0 0 . Continuing with our solution, we have
k 1 ( sin x ) b − 1 [ b sin ( a x ) cos x + a cos ( a x ) sin x ] = k 1 ( sin x ) 9 9 [ 1 0 0 sin ( a x ) cos x + a cos ( a x ) sin x ]
Recall the compound angle formula, sin ( A ± B ) = sin A cos B ± cos A sin B , so to combine 1 0 0 sin ( a x ) cos x + a cos ( a x ) sin x into a single expression, it is reasonable to assume that a = b = 1 0 0 .
= = = = k 1 ( sin x ) 9 9 [ 1 0 0 sin ( a x ) cos x + a cos ( a x ) sin x ] k 1 ( sin x ) 9 9 [ 1 0 0 sin ( a x ) cos x + 1 0 0 cos ( a x ) sin x ] k 1 0 0 ( sin x ) 9 9 [ sin ( 1 0 0 x ) cos x + cos ( 1 0 0 x ) sin x ] k 1 0 0 ( sin x ) 9 9 [ sin ( 1 0 0 x + x ) ] k 1 0 0 ( sin x ) 9 9 [ sin ( 1 0 0 1 x ) ]
Comparing it with the expression in question suggests that k = 1 0 0 as well. Double checking our work indeed shows that a = b = k = 1 0 0 works. Thus our answer is a + b + k = 3 0 0 .
Very unique !!
Problem Loading...
Note Loading...
Set Loading...
I = ∫ sin ( 1 0 1 x ) sin 9 9 x d x = ∫ sin ( 1 0 0 x + x ) sin 9 9 x d x = ∫ sin ( 1 0 0 x ) ( cos x ) ( sin 9 9 x ) d x + ∫ cos ( 1 0 0 x ) sin 1 0 0 x d x
Now on using Integration By Parts for first integral and leaving the second integral as it is, we get
I = 1 0 0 ( sin 1 0 0 x ) ( sin 1 0 0 x ) − ∫ cos ( 1 0 0 x ) sin 1 0 0 x d x + ∫ cos ( 1 0 0 x ) sin 1 0 0 x d x + c ∴ I = 1 0 0 ( sin 1 0 0 x ) ( sin 1 0 0 x ) + C